1994
DOI: 10.1128/iai.62.2.501-508.1994
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Actinobacillus actinomycetemcomitans leukotoxin expression: analysis of the promoter regions of leukotoxic and minimally leukotoxic strains

Abstract: The leukotoxin of Actinobacillus actinomycetemcomitans has been implicated as a virulence determinant in various human infections and is encoded by a multigene operon consisting of four known genes, designated ltxC, ltxA, ltxB, and ltxD. The ltx operon appears to be present in all A. actinomycetemcomitans strains, but levels of toxin expression vary greatly among strains. Thus, to gain a better understanding of the expression and regulation of the ltx operon, we have analyzed the ltx promoters of a highly toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
268
0
3

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(280 citation statements)
references
References 36 publications
9
268
0
3
Order By: Relevance
“…Hybridizations were carried out with ULTRAhyb (Ambion, Austin, TX) at 42 1C. Blots were probed with a 2.5-kbp fragment amplified from ltxA spanning nucleotides 644-3199 in the previously published ltxCA sequence (Brogan et al, 1994). Signal detection was carried out using anti-digoxigenin (DIG) alkaline phosphatase and CDP-Star (Roche Applied science, Indianapolis, IN) according to the manufacturer's instructions.…”
Section: Detection Of Ltxamentioning
confidence: 99%
“…Hybridizations were carried out with ULTRAhyb (Ambion, Austin, TX) at 42 1C. Blots were probed with a 2.5-kbp fragment amplified from ltxA spanning nucleotides 644-3199 in the previously published ltxCA sequence (Brogan et al, 1994). Signal detection was carried out using anti-digoxigenin (DIG) alkaline phosphatase and CDP-Star (Roche Applied science, Indianapolis, IN) according to the manufacturer's instructions.…”
Section: Detection Of Ltxamentioning
confidence: 99%
“…In addition to the leukotoxin, there is evidence to suggest that other components of A. actinomycetemcomitans are able to lyse PMNs. Brogan et al [51,52] have reported that the EDs0 for human PMNs of a 'non-leukotoxic' strain of the organism (NCTC 9710) is lower than that of a leukotoxic strain (Y4). This supports our finding that material obtained by saline extraction of strain NCTC 9710 was highly cytotoxic (EDs0 < 1.0 ng/ml) to human PMNs [57].…”
Section: Leukotoxinmentioning
confidence: 99%
“…The leukotoxin is encoded by an operon consisting of four genes, ItxC, ltxA, ItxB and ItxD. The ItxA gene encodes the leukotoxin itself, the ItxC gene may encode for an acyl carrier protein involved in acylation of the protein while the remaining two genes are probably involved in the transport of the toxin and its insertion into the membrane [51]. Nonleukotoxic strains have been found to contain all four genes of the Itx gene cluster.…”
Section: Leukotoxinmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical data indicate that LtxA is a major virulence factor in A. actinomycetemcomitans-mediated periodontitis (Haraszthy et al, 2000a;Haubek et al, 2001;. Thus, a particular clone of the bacterium, termed the JP2 clone, is strongly associated with aggressive periodontitis in adolescents of west-or north-African descent, and members of the JP2 clone have a characteristic 530 bp deletion in the promoter region of the ltx gene operon leading to highly increased production of LtxA (Brogan et al, 1994). LtxA is a member of the repeat-in-toxin (RTX) family of bacterial exotoxins, which molecular characteristics include the presence of glycine-rich nonapeptide repeats.…”
Section: Introductionmentioning
confidence: 99%